Feasibility of HPV vaccination program implementation: A qualitative study - Wiwin Lismidiati; Vivian Nanny Lia Dewi; Widyawati Widyawati; Wenny Artanty Nisman; Anis Widyasari; Ika Parmawati; Ova Emilia (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2022)
The implementation of the Human Papillomavirus (HPV) vaccination program is still experiencing obstacles in several developing countries. This setback is related to the lack of knowledge and the high cost of the vaccine so that it affects people's behavior about the HPV vaccine. HPV vaccination in adolescents itself as primary prevention has not been widely conducted by adolescents in Indonesia. The results of previous studies showed that not many teenagers had vaccinated against HPV by using self-financing guarantees such as health savings. The obstacles faced in implementing HPV vaccination are that the vaccine is still expensive and there is lack of knowledge of parents and adolescents about the importance of HPV immunization. This formative research using qualitative methods was conducted to analyze the implementation plan of the HPV vaccination program. Data were collected through focus group discussions (FGD) and in-depth interviews. At the end of each FGD activity or interview, transcription and thematic analysis based on content were done. The FGD participants were ten teachers, while the in-depth interview participants were one school committee. This study found two main themes, namely the scheme of implementing the HPV vaccination program and obstacles to the implementation of HPV vaccination. Schools generally supported the program implementation. However, parents still question the importance of the HPV vaccination for their daughters and consider the vaccine costs expensive. Implementation of the HPV vaccination program must consider the existing program schemes in schools and possible obstacles. The results suggested that for the next HPV vaccination program, the facilitators should provide intense and relevant education to parents about the importance and side effects of HPV immunization, and are expected to build a willingness of parents to vaccinate their daughters and seek vaccination costs, one of which can be through a savings program.